Quantity and quality of napping to mitigate fatigue and sleepiness among nurses working long night shifts: a prospective observational study - Kazuhiro Watanabe; Inaho Shishido; Yoichi M. Ito; Rika Yano (Journal of Physiological Anthropology)
Abstract Background Napping during night shifts is a countermeasure against fatigue and sleepiness, which both impact patient safety. However, there is insufficient evidence on how nurses nap, especially concerning their napping quality. This study explored night-shift napping and its associated factors among nurses, considering napping quantity and quality, to mitigate fatigue and sleepiness. Methods This month-long prospective observational study included 32 nurses working 16-h night shifts in a general ward. All nurses responded to questions on individual factors, while fatigue and sleepiness were checked four times during night shifts. Night-shift napping was measured using a wearable device and classified into six groups: time in bed [TIB] > 180 min and sleep efficiency [SE] ≥ 70%, TIB > 180 min and SE < 70%, TIB 120–180 min and SE ≥ 70%, TIB 120–180 min and SE < 70%, TIB < 120 min and SE ≥ 70%, and TIB < 120 min and SE < 70%. Results Most nurses (81.2%) worked four night shifts per month, and 105 night shifts in which nurses intended to nap were analyzed. The two nap conditions (TIB 120–180 min and SE ≥ 70%, TIB > 180 min and SE ≥ 70%) were not worse than other nap conditions in fatigue and sleepiness at the end of the night shift and change in fatigue from the start to the end of the night shift. Sleep reactivity, pre-nap time on electronic devices, and prophylactic naps taken before the night shift were each the common factors related to napping for TIB ≥ 120 min and SE ≥ 70%. Conclusions Nurses working long night shifts should consider both sufficient napping quantity and good napping quality. We suggest aiming for a TIB of at least 120 min and a SE of at least 70% to mitigate fatigue and sleepiness at the end of a night shift. Assessing sleep reactivity, pre-nap time on electronic devices, and prophylactic naps may be useful in achieving both quantity and quality effectively. Nurses and their managers should have a better understanding of napping and consider strategically taking naps during night shifts.